Chromosome X Open Reading Frame 38 (CXorf38) Is a Tumor Suppressor and Potential Prognostic Biomarker in Lung Adenocarcinoma: The First Characterization - Rui Yan; Heng-Wee Tan; Na-Li Cai; Le Yu; Yan Gao; Yan-Ming Xu; Andy T. Y. Lau (Proteomes)
Background: Previously, we found that an uncharacterized protein CXorf38 is significantly downregulated in human ZIP8-knockout (KO) cells. Given that ZIP8 regulates essential micronutrients linked to diseases including cancer, this study aims to characterize CXorf38 and evaluate its role in lung adenocarcinoma. Methods: iTRAQ-based proteomics was previously used to identify the abundance of proteins in ZIP8-KO cells. Cell proliferation and colony formation assays were used to examine the function of CXorf38 by overexpressing the gene in lung adenocarcinoma cell lines. Kaplan–Meier survival analysis was used to assess the prognostic value of CXorf38, while TCGA clinical database analysis was used to evaluate its expression in lung cancer tissues, particularly in smokers. Bioinformatics analyses (GO, KEGG, PPI, and ICI) were performed on CXorf38-coexpressed genes derived from patients with lung cancer. Results: CXorf38 overexpression suppressed lung cancer cell proliferation and colony formation, suggesting a tumor-suppressive role. Higher CXorf38 expression correlated with improved survival in patients with lung adenocarcinoma, but not in lung squamous cell carcinoma. Clinical data showed CXorf38 downregulation with lung cancer tissues of smokers, indicating a potential role in smoking-induced cancer progression and treatment. Functional analysis using bioinformatics linked CXorf38 to immune response regulation, suggesting involvement in the tumor immune microenvironment. Conclusions: Our study reveals for the first time that CXorf38 is a potential tumor suppressor, prognostic biomarker, and/or tumor immune regulator in lung adenocarcinoma—further research is warranted to explore its role in tumor immunity and its therapeutic potential.